Design and Modeling of a Compact Reconfigurable Slot Antenna for WLAN Portable Devices - Alnahwi, Falih M. (Basrah Journal for Engineering Sciences, 2017)
This paper presents design and modeling of a compact reconfigurable quarter wavelength slot antenna compatible with the portable devices of the 5GHz wireless local area network (WLAN) applications. The concept of the transverse resonant method which is used for the transmission lines is utilized for modeling the proposed slot antenna. A PIN diode is used to switch the antenna operating band from the lower unlicensed indoor 5GHz WLAN band (5-5.3) GHz to the upper one (5.7-5.9) GHz and vice versa. Another PIN diode is attached to the feed line to provide suitable matching stub length for each operation mode. Furthermore, the shape of the radiating slot of the proposed antenna is modified to provide an omnidirectional radiation pattern in the H-plane suitable for the portable gadgets of the WLAN system. The measurements are in well agreement with the simulated results, and they verify the precision of the suggested model and the enhanced matching characteristics for the two operation modes of the proposed antenna.